2018
DOI: 10.1088/1742-6596/1037/7/072011
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous Response and Mutual Interaction between Wind Turbine and Flow

Abstract: Abstract. The mutual fluid-structure interaction between wind turbine(s) and the highly turbulent flow deep inside a large wind farm is investigated in order to elucidate on how to implement and perform dynamic wind farm control. The study employs a fully coupled LES and aeroelastic framework, which provide time resolved flow and turbine response governed by a controller. The results show a large correlation between incoming flow and turbine response, which extends several radii upstream and could be utilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Conversely, large C T has a large impact on the flow development and therefore the maximum cross-correlation is significant reduced. This corresponds to previous results [28,29] where the cross-correlations are broken by the presence of the turbine. Second, the longest length scales typically have higher maximum cross-correlation, except at large downstream distances for high T SR, where the increased turbulence levels further break coherent structures of the inflow.…”
Section: Resultssupporting
confidence: 91%
“…Conversely, large C T has a large impact on the flow development and therefore the maximum cross-correlation is significant reduced. This corresponds to previous results [28,29] where the cross-correlations are broken by the presence of the turbine. Second, the longest length scales typically have higher maximum cross-correlation, except at large downstream distances for high T SR, where the increased turbulence levels further break coherent structures of the inflow.…”
Section: Resultssupporting
confidence: 91%
“…By using dynamic mode decomposition, which is related to the POD technique, Iungo et al (2015a) constructed a reduced-order model of the wind-turbine wakes embedded in a Kalman filter, and demonstrated the potential of this tool for real-time flow control in large-scale wind farms. Andersen and Sørensen (2018) found that the correlation between the instantaneous turbine performance and the upstream wake position is limited in very large wind farms, which they argue limits the benefits of wake steering as a control strategy, and point out that these results should be extended to cases in which intentional yaw misalignment is considered. In addition, they argued that the potential of induction-based control strategies should be further investigated.…”
Section: Introductionmentioning
confidence: 97%
“…Particularly for large turbines, modelling flexible deformation resulted in noticeable differences in blade loading, damage equivalent loads and power production for the AL, which were not seen for a standalone BEM tool, due to the ability of the blades to interact with the flow. Andersen and Sørensen (2018) studies correlations between inflow, turbine operation and wake flow, and demonstrates the importance of both having detailed knowledge of turbine inflow, and modelling the mutual turbine and flow interaction. In a comparison between fully resolved FSI simulations, measurement data and an aeroelastic blade element momentum (BEM) tool, Grinderslev et al (2021) likewise showed discrepancies between CFD-based FSI and BEM-based simulations in predicting blade loading due to complex inflow, indicating the importance of using higher-fidelity methods.…”
Section: Introductionmentioning
confidence: 99%